1997
DOI: 10.1152/ajpheart.1997.273.5.h2272
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular blood flow resistance: role of endothelial surface layer

Abstract: Observations of blood flow in microvascular networks have shown that the resistance to blood flow is about twice that expected from studies using narrow glass tubes. The goal of the present study was to test the hypothesis that a macromolecular layer (glycocalyx) lining the endothelial surface contributes to blood flow resistance. Changes in flow resistance in microvascular networks of the rat mesentery were observed with microinfusion of enzymes targeted at oligosaccharide side chains in the glycocalyx. Infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
161
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 19 publications
10
161
0
3
Order By: Relevance
“…increase in conductance likely reflects an increase in coronary vascular volume available for blood flow. Pries et al (1997) calculated that effective vessel diameter available for red blood cell and plasma motion had increased by at least 0.35-0.55 m after a single ϳ10 min infusion of heparinase in the rat mesentery bed. Indeed, a glycocalyx with these dimensions is typically reported in capillaries of cremaster tissue (6,21,30,31), and has been suggested to be present in myocardial capillaries as well (26).…”
Section: Rh Vs Ahmentioning
confidence: 99%
See 2 more Smart Citations
“…increase in conductance likely reflects an increase in coronary vascular volume available for blood flow. Pries et al (1997) calculated that effective vessel diameter available for red blood cell and plasma motion had increased by at least 0.35-0.55 m after a single ϳ10 min infusion of heparinase in the rat mesentery bed. Indeed, a glycocalyx with these dimensions is typically reported in capillaries of cremaster tissue (6,21,30,31), and has been suggested to be present in myocardial capillaries as well (26).…”
Section: Rh Vs Ahmentioning
confidence: 99%
“…However, it was shown that adenosine superfusion impaired glycocalyx exclusion properties (21). Because an intact glycocalyx strongly reduces the volume available for flow of plasma and red blood cells in capillaries (3,22,30), an impaired glycocalyx exclusion during adenosine is consistent with an increase in functionally perfused capillary volume, and as a result, elevated capillary tube hematocrit (12).The aim of the present study was to determine to which extent the glycocalyx limits coronary hyperemia obtained with adenosine compared with hyperemia obtained by an ischemic stimulus [reactive hyperemia (18)]. In anesthetized dogs, coronary pressure and flow were measured in the left circumflex artery, and reactive hyperemia was compared with the hyperemia induced by intracoronary injection of adenosine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that heparinase treatment reduced the fluorescence intensity of fluorescence-labeled wheat germ agglutinin by 27-51% [41] and the fluorescence intensity associated with the heparan sulfate antibody by 45.9% [40]. Furthermore, the thickness and negative charge of the glycocalyx were reduced by heparinase disruption [44].…”
Section: Effect Of Glycocalyx On Ec Monolayer Friction 321 Glycocalmentioning
confidence: 99%
“…This predicted value is larger than the wall shear stress exerted by the blood flow with a typical value of 2 Pa in a 6 lm capillary and smaller than the deforming stress of red blood cells with a typical value of 6 Pa. 71 This explains why the ESL can maintain its shape in blood flow but is crushed by motionless red blood cells in capillaries. 72 If we consider the film rigid, we can use the Sauerbrey equation. Using different resonant frequencies, the film thickness has different theoretical values: H 1 ¼ 118:0 nm, H 3 ¼ 98:3 nm, H 5 ¼ 88:5 nm, and H 7 ¼ 84:3 nm, where the subscripts denote the resonant order.…”
Section: -5mentioning
confidence: 99%